Through the Eyes of the Other: A Preservice Teacher's Journey Towards Multicultural Competence - Elizabeth Bifuh-Ambe; Paula Burnes (Networks: An Online Journal for Teacher Research, 2011)
There is an urgent need to prepare teachers to effectively meet the needs of diverse students in classrooms across the USA today. In response to this need, many teacher preparation institutions offer multicultural education (also referred to in the literature as diversity) courses that are geared towards providing prospective teachers with the necessary skills and dispositions necessary to meet the needs of diverse learners. Evidently, multicultural education is viewed as the solution to an educational system that puts many students at risk of failure due to their race, gender, exceptionalities, ethnicity, class, religion, language and sexual orientation (Banks, 1999; King, Hollins & Hayman, 1997; Melnick & Zeichner, 1997). However, the effectiveness of multicultural education courses in transforming pre-service teachers’ attitudes towards diverse students, or preparing them to meet the academic needs of these learners is debatable. This is due to a number of reasons: (a) the single subject approach to multicultural education that is obtained in many institutions is considered to be ineffective; (b) the attempt to re-conceptualize pedagogical approaches to embrace diverse perceptions in content, methods and assessment tools across all disciplines is often unsuccessful; (c) the initiative to re-conceptualize the university curriculum to reflect a broader range of human experiences is often met with resistance from some administrators, and teachers and students alike; and (d) some college professors who are competent in their subject areas and are willing to re-conceptualize their courses to foreground the multicultural component often lack the skills, experiences, and resources to do so (Bifuh-Ambe, 2006; Ladson-Billings & Tate IV, 1995).